2019
DOI: 10.13057/biodiv/d201215
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Cosmos sulphureus flower extract as a bioherbicide for Cyperus rotundus

Abstract: Abstract. Respatie. D. W, Yudono P, Purwantoro A, Trisyono Y.A. 2019. The potential of Cosmos sulphureus flower extract as a bioherbicide for Cyperus rotundus. Biodiversitas 20: 3568-3574. Cosmos (Cosmos sulphureus Cav.) flower is recognized as natural source of bioherbicide compounds for several weeds. The purple nutsedge (Cyperus rotundus L.) is an important weed, and this research was aimed to determine the effects of cosmos flower extract on this weed. Dried cosmos flowers were threshed and extracted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In general, each flower has approximately 15–30 flower tubes with a stalk length of 15 cm ( Hilmi et al, 2020 , Win, 2016 ). Recently, yellow cosmos has been reported to contain high levels of secondary metabolites, such as flavonoids, phenolics, tannins, and gallic acid, which can be used as natural pesticides and herbicides ( Aftab et al, 2021 , Respatie et al, 2019 , Saleem et al, 2017 ). Yellow cosmos produces daisy-like flowers with seeds atop long and slender stems.…”
Section: Introductionmentioning
confidence: 99%
“…In general, each flower has approximately 15–30 flower tubes with a stalk length of 15 cm ( Hilmi et al, 2020 , Win, 2016 ). Recently, yellow cosmos has been reported to contain high levels of secondary metabolites, such as flavonoids, phenolics, tannins, and gallic acid, which can be used as natural pesticides and herbicides ( Aftab et al, 2021 , Respatie et al, 2019 , Saleem et al, 2017 ). Yellow cosmos produces daisy-like flowers with seeds atop long and slender stems.…”
Section: Introductionmentioning
confidence: 99%
“…The common ornamental Cosmos species is Cosmos sulphureus Cav., i.e., yellow and orange flowers. Previous research showed that C. sulphureus can be used as refugial plants because they host natural enemies of some pests in rice (Aldini et al 2019), used as natural dyes, a source of pollen bees, and bioherbicides (Wroblewska et al 2016;Aldini et al 2019;Respatie et al 2019). The young leaves of C. sulphureus are consumed as vegetables; however, Cosmos caudatus Kunth.…”
Section: Introductionmentioning
confidence: 99%
“…The yellow cosmos contains high secondary metabolites such as phenolics, flavonoids, saponin, and tannins that can be used for biopharmaceutical and biopesticide applications (Saleem et al 2017;Aftab et al 2021). The previous study reported that yellow cosmos also contains gallic acid, which has the potential as a natural herbicide (Respatie et al 2019). The secondary metabolites of yellow cosmos can be increased through plant genetic transformation using the Agrobacterium-mediated technique.…”
Section: Introductionmentioning
confidence: 99%